Investigating the Use of Plain Language Summaries: A Case Study of a Selection of Canadian Science Journals - Bowker, Lynne (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2025)
Increasingly, researchers are encouraged to produce plain language summaries (PLSs) as a means of making research accessible to lay audiences. Canadian Science Publishing is a scholarly publisher of 22 journals that offers authors the option of creating PLSs. This article investigates how often authors who publish with Canadian Science Publishing take up that opportunity, and considers what factors might encourage or discourage their decision to produce a PLS. The article ends with a list of four recommendations that could promote increased production of PLSs in journals published by Canadian Science Publishing or other publishers.